Regulation of the catalytic activity of the human phosphatase PTPN4 by its PDZ domain. (30th September 2014) - Maisonneuve, Pierre; Caillet‐Saguy, Célia; Raynal, Bertrand; Gilquin, Bernard; Chaffotte, Alain; Pérez, Javier; Zinn‐Justin, Sophie; Delepierre, Muriel; Buc, Henri; Cordier, Florence; Wolff, Nicolas
<x xml:space="preserve">Abstract</x> The human protein tyrosine phosphatase non‐receptor type 4 (PTPN4) prevents cells death. Targeting its PDZ domain abrogates this protection and triggers apoptosis. We demonstrate here that the PDZ domain inhibits the phosphatase activity of PTPN4. The mere binding of a PDZ ligand is sufficient to release the catalytic inhibition. We combined analytical ultracentrifugation, small angle X‐ray scattering and NMR to understand how the PDZ domain controls PTPN4 activity. We show that the physiologically active PTPN4 two‐domain, encompassing the PDZ and the phosphatase domains, adopts a predominant compact conformation in solution. The PDZ ligand binding restores the catalytic competence of PTPN4 disrupting the transient interdomain communication. This study strengthens the emerging notion that PDZ domains can act as regulators of enzyme activity and therefore are active players in the dynamic regulation of signaling pathways. Structured digital abstract PTPN4_linker-PTP dephosphorylates pTyr peptide by enzymatic study (View interaction) PTPN4_PDZ-PTP dephosphorylates pTyr peptide by enzymatic study (View interaction)